THE DOUBLE STANDARDS OF INTERNATIONAL LAW: A COMPARATIVE STUDY OF THE CONFLICT IN UKRAINE AND PALESTINE - Aswadi, Khoitil (Tirtayasa Journal of International Law, 2023)
ABSTRACT:This study investigates the effect of double standards in international law on conflict resolution in Ukraine and Palestine. Through a comparison of conflicts in the two countries, this study finds that double standards in international law affect conflict resolution in Ukraine and Palestine differently. There is evidence of a double standard in international law related to the different interests of the major powers in the conflict in the two countries. The impact of this double standard affects the effectiveness of efforts to resolve the conflict in Ukraine and Palestine, with conflict resolution in Ukraine being achieved more quickly than in Palestine. Therefore, this research suggests the need for consistency and equality in the application of international law in dealing with conflicts, and seeking peace negotiations involving all parties involved in the conflict in order to achieve a sustainable resolution.Keywords: Double Standards, Conflict Resolution, Parties Involved.